PERANAN PEJABAT PEGAWAI NEGERI SIPIL BEA DAN CUKAI SEBAGAI PENYIDIK DALAM MENANGANI TINDAK PIDANA PENYELUDUPAN BARANG ELEKTRONIK TANPA IZIN DI KEPULAUAN RIAU - Ridho Aprison; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Based on the results of research conducted pre researcher at the Main Office of Customs and Excise Tanjung Balai Karimun known several cases of illegal smuggling of electronic goods from the period 2011-2015. Generally, electronic goods smuggled in the form of mobile phones, cameras and laptops. The ships were captured by the Customs and Excise Tanjung Balai Karimun does not have complete documents such as not having an Approval Letter of Goods (SPPB) and also has no other legal documents. Electronic goods illegally captured by the Customs and Excise Tanjung Balai Karimun seized for the purpose of investigation. During the period 2011 to 2015 every year period Customs and Excise Tanjung Balai Karimun always find the crime of smuggling of illegal electronic items that occurred in the jurisdiction of the Riau IslandsRole of Civil Servants (investigators) Customs and Excise Tanjung Balai Karimun in dealing with the crime of smuggling electronic goods without a permit in the Riau Islands, has been done with the maximum number of smuggling cases proven electronic goods without permission captured. In the process of investigation of Customs and Excise investigators guided in accordance with the applicable legislation under Article 112 of Law No. 17 of 2006 on Customs, Law Number 55 Year 1996 on the investigation in the field of Customs and Excise and in Article 7 of the Criminal Procedure Code.Obstacles encountered PPNS Customs and Excise Tanjung Balai Karimun in dealing with the crime of smuggling electronic goods without permission due to the mode that made the perpetrator, the breadth of the territorial waters of Indonesia, the facility destroyers patrol or less than the maximum, the investigator less power, the lack of understanding by the enforcement agencies Another law in some areas related to the implementation of the Customs and Excise enforcement and awareness less the law enforcement community about the smuggling. The efforts made by civil service officials and excise duty as an investigator in handling criminal offense smuggling electronic goods without permission in Riau Islands include: preventive measures, repressive efforts and provide the highest penalties for smugglersKeywords: role-PPNS-Smuggling